Three explanations for extraterrestrials: sensible, unlikely, mad. Issue 4 (5th October 2016) - Conway Morris, Simon
Abstract: The Fermi Paradox (or Question) has moved back into central focus. This is for a number of reasons, not least the evidence for both the abundance and antiquity of many extra-solar systems, the extrapolation of current technological trends to suggest that even inter-galactic colonization (by self-replicating machines) is plausible (if not desirable), and the recurrence of evolutionary solutions (convergence) in the terrestrial biosphere suggesting that features such as intelligence and tool-making are not fortuitous outcomes, but frequent if not universal. Here I review the three possible solutions to the Fermi Paradox. First, extraterrestrials certainly exist (and may be abundant), but for one reason or another (probably mundane) we have not yet met them, or at least found evidence for their existence. Second, against all expectations, we are alone. Third, we have entirely misunderstood the sort of universe we live in and have become unwitting hostages to a strict materialist explanandum that in refusing to acknowledge the other realities of our Universe has derailed any prospect of explaining the apparent absence of extraterrestrials.